Exploring Indicators of Successful Parenting of Adolescents among Iranian Families: A Qualitative Study - Masoud Asadi; Yazdan Mansourian; Ali Mohammad Nazary (Iranian Association of Health Education and Health Promotion, 2015)
Background & objective: In order to have effective parenting, which, in turn, results in children being happy, healthy and productive, it is necessary to design an effective indigenous pattern based on the Iranian culture. The aim of this study was to explore indicators of successful parenting of adolescents among Iranian families. Methods: This applied study used qualitative grounded theory to gather its data. 13 cases of successful parents were selected using theoretical sampling. They were studied using in-depth interviews over a period of 6 months. After collecting the data, they were recorded and coded in terms of categories, and then they were classified. In analyzing the data, the original codes were identified and based on axial coding, categories of parental role were identified. Results: In the context of the role of parents, appreciation, encouraging, sincerity, positive communication, navigation, responsibility, fairness, monitoring, control and modeling role of parents were identified as parenting indicators. Conclusion: The findings of this study can be helpful for parents in the upbringing of healthy young adults. Family counselors and psychologists could also apply the results of this study for educating families for successful parenting. Paper Type: Research Article